P14.70 Systemic therapy for brain metastases in elderly patients with lung cancer: A systematic review - Nakasu, Y (Neuro Oncol, 2019)
BACKGROUND: Brain metastases (BM) account for the majority of intracranial malignant tumours in the elderly. Almost 50% of BM originate from lung cancer, particularly non-small cell lung cancer (NSCLC). The objective of this review is to summarize the involvement of elderly patients in emerging systemic therapies especially targeted therapies for the treatment of BM from NSCLC. MATERIAL AND METHODS: PubMed database was searched from 2008 to December 2018. Randomized controlled trials and systematic reviews for BM from NSCLC treated with targeted therapy were included. RESULTS: A total of 85 studies were evaluated for eligibility, and 23 publications met the eligibility criteria and were screened for inclusion. Of these, only two phase-III studies met all the criteria (Sperduto 2013, Yang 2017), and three other studies of subgroup analysis of trials were focused on BM (Schuler 2016, Gadgeel 2018, Camidge 2018). In the 23 papers, eligibility criteria for age were from 18 years to 75 years old or no upper limits. Actual mean or median ages ranged 51 to 64 years. Population of patients with active BM consisted none to 100% in each study. The two phase-III studies focused on treatment of BM, median ages were 63 and 57 years. The latter reported a TKI showed significantly longer intracranial PFS and no difference in HR was found in age groups older or younger than 60 years. In the three papers of subgroup analysis, response rate of BM or intracranial distant recurrence were examined. Median ages were 51 to 62 years, ranged from 18 to 86 years. However in these analytical efforts, no results were reported about age as an outcome factor. CONCLUSION: Patients with active or treated BM have become included in randomized controlled trials of systemic pharmacotherapies. Elderly patients also have become included in trials. However, outcomes focused on BM are not clearly understood especially in elderly patients. We need prospective studies and assessment of targeted therapy for elderly patients with BM for better understanding of treatment strategies and options for those patients increasing in number.